Mediterranean, Migrations and Economic Development - SCHILIRÒ, Daniele (Journal of Advanced Research in Economics and International Business; Vol 3 No 4 (2015): JAREIB, Volume III, Issue 4, 2015, 2015)
The economic development of the Mediterranean countries, particularly those on the south shore, is the theme of this contribution and is closely linked to the issue of migration that has become an important problem in recent years with dramatic implications for the entire area. The policies promoted by the European Union towards the countries of the South shore have essentially failed their goal. Italy can play an important role in the Mediterranean context, given its geographic and political location, taking appropriate initiatives and promoting dialogue and a closer North-South relationship. This contribution addresses the issue of economic development and the problem of migrations in the countries of the Southern Mediterranean and the effects that these problems have on European countries, trying to identify the most appropriate policies. Specifically, the paper discusses the demographic issue and the migration issue affecting the countries on the southern shore of the Mediterranean. It also analyzes the Mediterranean economy and, above all, the theme of the economic development of countries on the southern shore, and it seeks to find solutions to improve economic conditions and use of resources in this Mediterranean region.